780 Contributions of dermal vs air exposure to biomonitoring for solvent exposure. (24th April 2018) - Creta, Matteo; Moldovan, Horatiu; Voidazan, Septimiu; Godderis, Lode; Duca, Radu Corneliu; Vanoirbeek, Jeroen
Abstract : Introduction: Dermal exposure assessment is becoming increasingly important in occupational settings, but its contribution to the overall body burden is not yet well-established. Therefore, we evaluated the contribution of dermal exposure to the total body burden as reflected by biomonitoring, by simultaneous quantitative assessment of dermal, and air exposure in combination with bio- monitoring, in workers exposed to solvent. Methods: Exposure to the volatile organic compounds, styrene, acetone and toluene on the skin was evaluated using activated charcoal cloth patches; inhalation exposure was measured using passive organic vapour monitors, and systemic exposure was assessed by quantification of mandelic acid, acetone and hyppuric acid in urine, as biomarkers for styrene, acetone and toluene, respectively. Exposure was measured in 40 workers performing different tasks: hydraulic press (HP) workers, sheet moulding composite (SMC) workers, mechanics and office workers in a thermoplastic panels factory. Results: For styrene, the dermal exposure levels found were higher for HP workers (1532±450 μg/cm 2 ) than for the other workers (e.g. SMC 179±50). Inhalation exposure levels for HP and SMC workers were similar (58±11 mg/m 3 and 60±8 mg/m 3, about 70% TLV), but urinary concentrations of mandelic acid were higher for HP (549±85 µg/mL) then SMC (331±21 µg/mL) workers. In addition, a good correlation between dermal, air and urinary levels of acetone was found. Unlike for styrene and acetone, toluene levels in air were less than 1% TLV, regardless of the tasks performed by the workers. No relevant dermal or inhalation exposure was found for mechanics and office workers. Discussion: This study shows that for solvents, high dermal exposure substantially contributed to the increased concentrations of urinary metabolites. Therefore, the contribution of dermal exposure to the overall body burden is as important as the respiratory exposure, especially for less-volatile solvents, such as styrene.